Efforts to Improve Early Childhood Art Development Through Finger Painting Media for Class B Children in Ra Al Hidayah Rempek Academic Year 2022/2023 - Fauziah, Humaeratul; Alawiyah, Tuti; Marzoan, Lalu (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This research aims to improve children's drawing skills through finger painting media for group B children at RA Al Hidayah Rempek for the 2022/2023 academic year. The subjects of this research were group B children at RA Al Hidayah Rempek with a total of 14, namely 7 boys and 7 girls. The research method used is the Classroom Action Research Method (PTK), which is research carried out regularly on various actions carried out by teachers to improve learning conditions. The data in this research was collected using the observation method as the main method, interviews and documentation methods as complementary methods. The results of this research show that there is an increase in the artistic abilities of group B children, especially in drawing activities. In the pre-cycle classical completion only reached 21.4%, in cycle I children's art drawing ability increased by 28.6% to 50%, and in cycle II children's art drawing ability increased by 14.2% to 64.2% . Continuing in cycle III, it increased by 21.4% to 85.7%. This shows that there has been an increase in the percentage of children's drawing skills that are at the criteria of developing according to expectations (BSH) with a percentage of 85.7% achieved in this study. Which means that the majority of children are able to draw using finger painting media at RA Al Hidayah Rempek, North Lombok Regency, 2022/2023 Academic Year. Kata Kunci : Kemampuan Seni Menggambar, Media Finger Painting